2022
DOI: 10.1002/anie.202206399
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenised Molecular Catalysts for Sustainable Electrochemical CO2 Reduction

Abstract: There has been a rapid rise in interest regarding the advantages of support materials to protect and immobilise molecular catalysts for the carbon dioxide reduction reaction (CO2RR) in order to overcome the weaknesses of many well‐known catalysts in terms of their stability and selectivity. In this Review, the state of the art of different catalyst‐support systems for the CO2RR is discussed with the intention of leading towards standard benchmarking for comparison of such systems across the most relevant suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 108 publications
(44 reference statements)
0
42
0
Order By: Relevance
“…However, moving forward to applications, it is often better to design systems in which the molecular catalyst is heterogenized on the electrode (or photoelectrode) surface . Different strategies have been developed to immobilize molecular catalysts including embedment in a three-dimensional polymeric structure deposited on the electrode surface, physical adsorption exploiting π–π and other electrostatic interactions or covalent direct binding to the electrode surface. , Among the variety of molecular linking groups, allowing the catalyst immobilization on the electrode surface or in an electrode material, aryldiazonium, amine, alkynyl, sulfonyl thiol, phosphonates, and carboxylates can be used . When the catalyst is, as it is often the case, a transition metal complex, one of these immobilizing groups has to be linked to the complex through the ligands, and an important question is thus raised on its influence on the redox properties and on the catalytic properties of the immobilized complex response.…”
Section: Introductionmentioning
confidence: 99%
“…However, moving forward to applications, it is often better to design systems in which the molecular catalyst is heterogenized on the electrode (or photoelectrode) surface . Different strategies have been developed to immobilize molecular catalysts including embedment in a three-dimensional polymeric structure deposited on the electrode surface, physical adsorption exploiting π–π and other electrostatic interactions or covalent direct binding to the electrode surface. , Among the variety of molecular linking groups, allowing the catalyst immobilization on the electrode surface or in an electrode material, aryldiazonium, amine, alkynyl, sulfonyl thiol, phosphonates, and carboxylates can be used . When the catalyst is, as it is often the case, a transition metal complex, one of these immobilizing groups has to be linked to the complex through the ligands, and an important question is thus raised on its influence on the redox properties and on the catalytic properties of the immobilized complex response.…”
Section: Introductionmentioning
confidence: 99%
“…The local coordination environment, serving as the pivotal factor to estimate the structure–activity relationships on metallic active sites with different coordination configuration, is capable of regulating catalytic selectivity between the ECO 2 RR and competing HER. 79 The experimental and theoretical research on functional porous frameworks resulted in the fundamental comprehension of structure–activity relationships, which can guide the rational design of active sites with enhanced intrinsic activity for the ECO 2 RR. 80 Generally, it has been demonstrated that the elaborate design and preparation of functional porous frameworks can produce the expected site configuration for the ECO 2 RR, which is one of the effective strategies that decides the catalytic selectivity for the ECO 2 RR.…”
Section: Design Strategies Of Functional Porous Frameworkmentioning
confidence: 99%
“…All these supports can improve the current transmission and selectivity (for example CO, HCOOH, HCHO, CH 3 OH, CH 4 , C 2 H 4 , C 2 H 6 and C 2 H 5 OH) of the catalyst. [59] For instance, Wang et al [60] found a method to rationally assemble the catalytic interface by incorporating Cu nanoparticles into NÀ Nd to obtain NÀ Nd/Cu by rationally adjusting nitrogen-doped nanodiamond and copper nanoparticles, as shown in Figure 4a. Based on the experimental study, it was found that the conversion of CO 2 gas to C 2 oxygenator did occur at the interface because of the complementary effect of both components.…”
Section: Metal-support Interactions (Msi) Effectmentioning
confidence: 99%
“…The catalyst supports are mainly divided into four categories, such as carbon‐based support, metal organic frameworks or covalent organic frameworks porous supports, TiO 2 support and polymer gel support. All these supports can improve the current transmission and selectivity (for example CO, HCOOH, HCHO, CH 3 OH, CH 4 , C 2 H 4 , C 2 H 6 and C 2 H 5 OH) of the catalyst [59] . For instance, Wang et al [60] .…”
Section: Regulating and Controlling Co2rr Strategies And Mechanismmentioning
confidence: 99%